The Influence of Grit and Mathematical Connection Skills on Students' Mathematical Critical Thinking - Nurma Izzati; Wildan Ahmad Nur Fauzan (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
This study was designed to investigate the impact of grit and competence in mathematical connectivity on students' mathematical critical reasoning abilities, both separately and in combination. A quantitative approach through a correlational survey was applied in this study. The respondents of this study were all eighth-grade students at MTs N 1 Kuningan, of which 25 students were selected as samples through a purposive sampling technique. The measuring instruments used included a questionnaire on grit, a test instrument to evaluate mathematical connection competence, and a test instrument to measure mathematical critical thinking capabilities. All instruments have undergone validity and reliability tests, and meet the standards of suitability for use. Data analysis was conducted using multiple linear regression techniques, preceded by analysis prerequisite tests including normality, multicollinearity, and heteroscedasticity tests, where all assumptions were met. The research findings show that individually, grit has a significance value of 0.834 (p>0.05) and mathematical connection ability has a significance value of 0.591 (p>0.05), which means that both variables do not have a major impact on mathematical ability. Simultaneously, the ANOVA test results obtained an F value = 0.247 with a significance of 0.784 (p>0.05), which indicates that the regression model is not significant. The R Square value of 0.022 indicates that only 2.2% of the variation in mathematical critical thinking ability can be attributed to grit and mathematical connection ability, while 97.8% is influenced by other factors outside the study. Thus, the research hypothesis is rejected. This study indicates that grit and mathematical connection skills were not proven to be significant predictors of students' mathematical critical thinking skills in the context of the sample studied. The researchers recommend that future research use a larger sample size and incorporate other variables such as learning motivation, learning independence, or self-efficacy.